Partial Breast Reconstruction with Goldilocks Technique After Excision of Giant Fibroadenoma: A Case Report - Ter Louw, Ryan P. (Plast Reconstr Surg Glob Open, 2017)
Giant juvenile fibroadenomas are relatively rare, accounting for less than 1% fibroadenomas. Large breast tumors create significant asymmetry and provide unique reconstructive challenges after removal. In this case, we describe a 21-year-old female with delayed presentation of a giant fibroadenoma of the right breast. This represents an unusual presentation of benign breast disease requiring reduction of the skin envelope, extensive glandular resection, lower pole reconstruction, and free nipple grafting to achieve symmetry with the opposite breast. A novel modification of the Goldilocks mastectomy technique is described for partial breast reconstruction. Adaptation of the Goldilocks mastectomy technique provides adequate soft tissue for partial breast reconstruction. Using the lower pole deepithelialization breast skin flap provides autologous vascularized tissue to supplement volume loss after tumor and glandular excision. Benign breast disease can create significant breast deformities. Application and combination of the Goldilocks mastectomy technique allow for partial breast reconstruction without the need for an additional donor site or prosthetic devices.